Low-Carbon Development : Opportunities for Nigeria - Cervigni, Raffaello (Washington, DC: World Bank, 2013)
The Federal Government of Nigeria (FGN) has formulated an ambitious strategy, known as Vision 20: 2020, which aims to make Nigeria the world s 20th largest economy by 2020. This book argues that there are many ways that Nigeria can achieve the Vision 20: 2020 development objectives for 2020 and beyond, but with up to 32 percent lower carbon emissions. A lower carbon path offers not only the global benefits of reducing contributions to climate change, but also net economic benefits to Nigeria, estimated at about 2 percent of gross domestic product (GDP). The FGN and the World Bank agreed, as part of the Country Partnership Strategy (CPS) 2010-13, to conduct an analysis of the implications of climate change for Nigeria's development agenda. The current volume focuses on low-carbon development. Building on the work under way on Nigeria's nationally appropriate mitigation actions, the authors evaluate opportunities to pursue national development priorities using technologies and interventions that reduce emissions of greenhouse gases (GHGs), referred to here as low-carbon options. The document is structured as follows: chapter one is introduction; chapter two provides essential background on the country and the economic sectors. Chapter three describes the analytical approach, providing a summary of how the scenarios were developed, methods of analysis, models, and the data and general assumptions used. Chapters four-seven present the analysis and results for each sector: agriculture and land use, oil and gas, power, and transport, respectively. Each chapter provides an introduction to the sector and the approach, findings, and recommendations for options and actions for low-carbon development. Chapter eight summarizes the key findings across sectors. It describes the main scenarios that were modeled across all sectors and their implications for GHG emissions and the economy. It provides general recommendations on how Nigeria can reconcile national growth objectives with low-carbon development using a cross-sector perspective.